Application of energy ratios to improve ventilation in the Huaron Mine - Baca Mena, Alexis (2022)
This research seeks to optimize production and ventilation in the mining industry using the energy and production ratios method. To do this, it estimates the energy consumption in ventilation, obtaining the production ratios in the Huaron unit and applying the energy and production ratios to determine the efficiency of consumption in each area, achieving a cost comparison to achieve an efficient distribution. of ventilation, it also recommends ways to optimize energy consumption for ventilation by using energy and production ratios.   Through this methodology, it has been possible to maintain the energy and production ratio below 2.9 US$/TMS, optimizing energy consumption in the 3 operating zones of Huaron, likewise, it allowed efficiency in the consumption of each zone of the mine. , through which it was able to generate savings in energy consumption of 35 million kWh/month to 30 million kWh/month, which in economic terms corresponds to a saving of US$ 358,000 dollars for the unit Huaron.